2014
DOI: 10.1177/1403494814563370
|View full text |Cite
|
Sign up to set email alerts
|

Are weight-related attitudes and behaviours associated with the accuracy of BMI derived from self-reported weight and height among 13-year-olds?

Abstract: weight perception and weight control behaviour among girls only were related to the accuracy of self-reported BMI; no association was found with self-weighing behaviour and the perceived importance of weight for how adolescents perceive themselves. Knowledge of such factors will allow for a better interpretation and possibly adjustment/correction of results of surveys based on self-reported weight and height data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…After removal of duplicates, 1751 were left for screening of titles and abstracts, from which ninety-five articles were retrieved for full-text screening. Finally, thirty-seven studies were found to have met all the selection criteria ( 18 , 24 41 , 43 49 , 59 – 69 ) .
Fig. 1Flowchart showing selection of studies for inclusion in the current meta-analysis (BMI sr , BMI derived from self-reported height and weight; BMI m , BMI derived from measured height and weight)
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of duplicates, 1751 were left for screening of titles and abstracts, from which ninety-five articles were retrieved for full-text screening. Finally, thirty-seven studies were found to have met all the selection criteria ( 18 , 24 41 , 43 49 , 59 – 69 ) .
Fig. 1Flowchart showing selection of studies for inclusion in the current meta-analysis (BMI sr , BMI derived from self-reported height and weight; BMI m , BMI derived from measured height and weight)
…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates, 1751 were left for screening of titles and abstracts, from which ninety-five articles were retrieved for full-text screening. Finally, thirty-seven studies were found to have met all the selection criteria (18,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(43)(44)(45)(46)(47)(48)(49)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) .…”
Section: Resultsmentioning
confidence: 99%
“…Objective measurements of body weight parameters were conducted in 21 of the 28 included studies, which was a strength of these studies, as self‐report measures of adiposity are known to underestimate weight and lead to significant misclassifications of OW and OB . However, no evidence of validity or reliability was provided for the measures of mediators in most of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an alarmingly low percentage of the sample met the recommended level of physical activity and the dietary recommendations (and the percentage was lower than reported in other national and international studies of adolescents). 3,11,50 Together with the lower cardiorespiratory fitness and higher BMI than found in previous studies, 33,51 this indicates a general poor physical health profile in the sample. Reported sleep was more in accordance with findings from other studies of the same age group, 52 as were the mean READ total and subscale scores.…”
Section: Discussionmentioning
confidence: 78%